Textile Industry as a Smart Specialization of Lodz and the Region of Catalonia - Makary Piasecki (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2016)
The subject discussed in this paper concerns the situation of small and medium enterprises (SMEs) in the textile and chemical treatment industries in Lodz and Catalonia. This paper refers to the case of external environment factors that significantly impact these enterprises. It also addresses problems of technology transfer, barriers and opportunities resulting from partnership with public sector. This research is based on literature studies and empirical view on the environment of these two industries. It employs a method of open interviews with experts representing the private and public domain in order to identify key factors that influence that segment of activity. This paper has a structure of an international comparison of two similar regions in Poland and in Spain, which are pioneers of high technology textile services and chemical treatment.